Mechanical Properties and Deterioration Instability of Filling Body with Gangue-Cement Material Based on AE Experiment. (5th January 2022) - Yu, Guofeng; Han, Yunchun; Yu, Xiaoyang; Bao, Ren; Guo, Jiaxing; Feng, Qingbo
Abstract : Gangue materials have been used to solve mine disasters with a support tunnel along the goaf and filling mining. Mastering the properties and damage characteristics of filling materials is an important basis for effective implementation. Based on the conventional uniaxial compression acoustic emission (AE) test, the effects of cementitious materials, ratio between water and cementitious material, gangue particle size, and grading parameters on the mechanical properties of gangue-cement samples were analyzed. The stage characteristics of compression deformation were studied. The fracture propagation characteristics and rock mass failure types induced by different graded gangues were revealed. The fracture forming mechanism from clustered damage and failure was interpreted. The results show that the compressive strength of the backfill increases with the increase of cementitious material; however, it decreases with the increase of water binder ratio. Controlling the proportion and dosage of materials was the key factor to realizing pumpability and stability. Combined with the deformation and AE characteristics, the failure stage of the backfill body is divided into three stages: linear deformation-low energy changing, block compression-high energy changing, and gentle stability-stable energy changing. Affected by the gangue distribution, the load in each stage will induce fracture to produce five distribution modes of single, turning, breakthrough, bifurcated, and collapsed surrounding gangue. In the process of loading failure, different gradation and particle sizes will also change its stress concentration characteristics, resulting in the transformation of rock failure types. The surface structure and roughness of gangue play an important role in the compressive performance of cement paste. The research results try to provide some guidance for efficient filling mining.